Pengaruh Audit Fee, Audit Tenure, Komite Audit, Rotasi Audit Terhadap Kualitas Audit pada Perusahaan LQ45 - Maulidatul Mutamimah; Nawang Kalbuana; Yoyok Cahyono (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This research is a quantitative study using secondary data through access to the Indonesia Stock Exchange website or the official website of the relevant company, which aims to determine the effect of audit fees, audit tenure, audit committee, audit rotation on audit quality. The sample of this research is LQ45 companies listed on the Indonesia Stock Exchange from 2019 to 2023. This study used purposive sampling technique in determining the sample, resulting in 29 companies from a total population of 45 companies. Meanwhile, logistic regression analysis was used to conduct the analysis. The data processing process uses SPSS version 23. The t test results (partial) show that the audit fee variable has an effect on audit quality. Meanwhile, the audit tenure, audit committee, and audit rotation variables have no effect on audit quality. The results of the f test (simultaneous) show that the variables audit fee, audit tenure, audit committee, audit rotation simultaneously affect audit quality.